2017
DOI: 10.21037/jtd.2017.05.78
|View full text |Cite
|
Sign up to set email alerts
|

Does the usage of digital chest drainage systems reduce pleural inflammation and volume of pleural effusion following oncologic pulmonary resection?—A prospective randomized trial

Abstract: Background: Prolonged air leak and high-volume pleural drainage are the most common causes for delays in chest tube removal following lung resection. While digital pleural drainage systems have been successfully used in the management of post-operative air leak, their effect on pleural drainage and inflammation has not been studied before. We hypothesized that digital drainage systems (as compared to traditional analog continuous suction), using intermittent balanced suction, are associated with decreased pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Five studies evaluated the incidence of prolonged air leak [11, 12, 14, 16, 17]. Digital chest drainage system significantly reduced the risk of prolonged air leak compared with traditional chest drainage system (RR = 0.54, 95%CI 0.40–0.73, p < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies evaluated the incidence of prolonged air leak [11, 12, 14, 16, 17]. Digital chest drainage system significantly reduced the risk of prolonged air leak compared with traditional chest drainage system (RR = 0.54, 95%CI 0.40–0.73, p < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). Among the five studies, four studies were randomized control trials [11, 12, 16, 17], in this subgroup, the risk of prolonged air leak was still lower in digital group than in traditional group (RR = 0.59, 95%CI 0.43–0.82, p = 0.002). One study was observational study [14], which the risk of prolonged air leak was also lower in digital group than in traditional group (RR = 0.33, 95%CI 0.15–0.75, p = 0.008).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of digital chest drainage systems on outcomes after pulmonary resection was studied in a trial including 103 patients who were randomized to either analog or digital drainage systems (De Waele et al 2017 ). The use of digital systems had no significant effect on pleural fluid formation, but was associated with a significantly lower incidence of prolonged air leakage, compared with analog systems (3.8% versus 18%, respectively, P = 0.025).…”
Section: Postoperative Carementioning
confidence: 99%
“…In these and other studies, the digital drainage systems were shown to be safe, consistent, and reliable in the detection of air leaks, allowing for earlier removal of chest tubes in the postoperative patient population. 20 However, the cost effectiveness remained unanswered.…”
Section: Digital Drainage Systemsmentioning
confidence: 99%